A marca da violência e a reincidência na medida socioeducativa - Silva, Lúcia Helena Anastácio da (2007)
The imprint of violence and its repetitive strain, on a social/educational aspect of youngsters, guilty of misdemeanours, targets of violence and possible explications for such behavior, juvenile criminality and hostile integration . We outlive a brief history of juridical aspects of repeated crime and its relationship to the social/penal process on minors, from the Empire to the coming of ECA, stressing the "Minorist Law" and child and youth instituanalizing until current FEBEM (State Juvenile Foundation). Theoretical forms also aims at analysis, marks, prejudice and social exclusion categories, in the light of Goffman (1988) and Sposati (2000). Methodology used in the research, was quality approach, based on six youngsters, who deal with their paths, motivation and interpretation of lived life experiences, coaching them into reflection on reincidence in crime, such approach having themselves as starting point. We try to fathom how repetitive social behavior, is the result of how global universe is deemed by these in question, values and judgments, reinterpreted from their own life experience and of their own perception of breaching possibility from this pattern